2008
DOI: 10.1063/1.2919784
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz characterization of multi-walled carbon nanotube films

Abstract: Multi-walled carbon nanotube films are characterized using terahertz time-domain spectroscopy. Both transmission and reflection experiments are performed in order to measure both the complex refractive index and the wave impedance. This method allows simultaneous extraction of both the permittivity (ε=ε′−iε″) and permeability (μ=μ′−iμ″) without any assumptions. Experimental results are obtained from 50 to 370 GHz and compared well with the microwave data (8–50 GHz) of the same sample measured using a vector ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…For example, in the case of normal incidence, the zeroth-order transmission coefficient , and the first-order coefficient due to one time of Fabry-Perot reflection, can be expressed as (see [14]) where is the frequency, is the sample thickness, is the speed of light, and is the refractive index of the sample. Because the foam sample has a refractive index close to 1 (free-space) the first-order term and all higher order terms are close to zero, and thus indistinguishable as separated pulses in the output time-domain waveform.…”
Section: Dielectric Materials Property Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the case of normal incidence, the zeroth-order transmission coefficient , and the first-order coefficient due to one time of Fabry-Perot reflection, can be expressed as (see [14]) where is the frequency, is the sample thickness, is the speed of light, and is the refractive index of the sample. Because the foam sample has a refractive index close to 1 (free-space) the first-order term and all higher order terms are close to zero, and thus indistinguishable as separated pulses in the output time-domain waveform.…”
Section: Dielectric Materials Property Determinationmentioning
confidence: 99%
“…In the data extraction, it is found that after the second term is included, the solution converges. The rest of the extraction is simply fitting the term with the measured complex transmission coefficient numerically, and determine the value of complex at each frequency ( [14]). Once the refractive index is extracted, the sample permittivity is obtained as .…”
Section: Dielectric Materials Property Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since no magnetic behavior is expected from the material, its permeability μ = 1. The complex permittivity was determined by performing a single transmission experiment using THz-TDS [17][18][19][20]. The dielectric constant ε" and the loss tangent tan δ = ε""/ε" (a convenient parameter representing the loss in a dielectric material) were extracted from the measured magnitude and phase of the transmission coefficient of the block polymer material.…”
Section: Dielectric Materials Property Determinationmentioning
confidence: 99%
“…The MWCNT papers have reported studies in the 8-50 GHz range [1,5]. MWCNTs deposited on a silicon wafer have been measured in the X-band (8-12 GHz) [6].…”
mentioning
confidence: 99%